The concept of work in the theological teachings of Rabbi Avraham Yitzchak Kook - Mashiach, Amir (HTS teologiese studies, 2020)
This article aims to understand the concept of work in the teachings of Rabbi Avraham Yitzchak Hacohen Kook (1865–1935). As the person who had the maximum impact on the religious Zionist sector, with its guiding principle of Torah va’avodah, meaning Torah and work, it is necessary to clarify his attitude towards work. Did he perceive work as a necessity, a part of one’s duty to support the members of the household, or perhaps also as an ideological value, part of a worldview that combines religious values with extra-religious values, or then again maybe he perceived work as a religious value? This article shows that R. Kook’s positive attitude towards work differs from traditional perspectives on work because of a pantheistic influence. Pantheism made him redefine the boundaries of Torah and include work and materiality.